2020
DOI: 10.33549/physiolres.934401
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Cough Reflex by Gaba-Ergic Inhibition in Medullary Raphé of the Cat

Abstract: We studied the effects of GABA receptor agonists microinjections in medullary raphé on the mechanically induced tracheobronchial cough response in anesthetized, unparalyzed, spontaneously breathing cats. The results suggest that GABA-ergic inhibition significantly contributes to the regulation of cough reflex by action of both GABAA and GABAB receptors. The data are consistent with inhomogeneous occurrence of GABA-ergic neurons in medullary raphé and their different involvement in the cough reflex control. Cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
2
1
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…It is also a positive regulator of the secretion of GABA, an inhibitory neurotransmitter with anti-inflammatory activity 32 . Animal models 51,52 and controlled trials 53,54 have demonstrated that agonists to GABA receptors inhibit the cough reflex; specifically, baclofen has been shown to supress ACEI-induced cough 55 . Further, INHBC is expressed in the nervous system and is known to suppress inflammatory pain responses 42 and current evidence demonstrates the role of BTBD11 in regulating glutamatergic synapse function 43 .…”
Section: Discussionmentioning
confidence: 99%
“…It is also a positive regulator of the secretion of GABA, an inhibitory neurotransmitter with anti-inflammatory activity 32 . Animal models 51,52 and controlled trials 53,54 have demonstrated that agonists to GABA receptors inhibit the cough reflex; specifically, baclofen has been shown to supress ACEI-induced cough 55 . Further, INHBC is expressed in the nervous system and is known to suppress inflammatory pain responses 42 and current evidence demonstrates the role of BTBD11 in regulating glutamatergic synapse function 43 .…”
Section: Discussionmentioning
confidence: 99%